Prozessentwicklung zur Gewinnung von Oxymethylenethern (OME) aus Methanol und Formaldehyd - Oestreich, Dorian (KIT Scientific Publishing, 2017)
The present work covers fundamental issues such as OME synthesis and properties up to process development and optimization for oxymethylene ethers (OME) production. This innovative diesel fuel can be produced from renewable raw materials. Compared to conventional diesel, OME leads to a significant reduction of nitrogen oxides and soot formation.